2013
DOI: 10.1017/s1368980013003169
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean diet and health status: an updated meta-analysis and a proposal for a literature-based adherence score

Abstract: Objective: To update previous meta-analyses of cohort studies that investigated the association between the Mediterranean diet and health status and to utilize data coming from all of the cohort studies for proposing a literature-based adherence score to the Mediterranean diet. Design: We conducted a comprehensive literature search through all electronic databases up to June 2013. Setting: Cohort prospective studies investigating adherence to the Mediterranean diet and health outcomes. Cut-off values of food g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
650
3
16

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 836 publications
(726 citation statements)
references
References 43 publications
21
650
3
16
Order By: Relevance
“…In fact, participants in 274 the upper baseline quartiles of MDP followed a diet rich in plant based foods and poor in 275 animal foods, and had the lowest risk of mortality. Third, the available evidence about olive 276 oil, suggests that it plays a role in the prevention of coronary heart disease, and cancer, and 277 may influence survival [1,2,21,22,25] . Besides, olive oil and particularly EVOO improves 278 the lipid profile and has potent antioxidant and anti-inflammatory properties [27,28] .…”
Section: Discussion 224mentioning
confidence: 99%
“…In fact, participants in 274 the upper baseline quartiles of MDP followed a diet rich in plant based foods and poor in 275 animal foods, and had the lowest risk of mortality. Third, the available evidence about olive 276 oil, suggests that it plays a role in the prevention of coronary heart disease, and cancer, and 277 may influence survival [1,2,21,22,25] . Besides, olive oil and particularly EVOO improves 278 the lipid profile and has potent antioxidant and anti-inflammatory properties [27,28] .…”
Section: Discussion 224mentioning
confidence: 99%
“…Numerous studies have shown the health-promotion and diseaseprevention characteristics of the Mediterranean diet (MD) [1][2][3]. The MD has been postulated as a protective factor against different diseases, including hypertension and coronary heart disease [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary patterns can be defined in a number of ways including general principals and descriptions of the diet, a priori scoring systems, a posteriori dietary pattern formation, dietary pyramids or by food and nutrient analysis [53, 65-67, 70, 71]. Over the past several years, adherence to the MedDiet has been estimated mainly through the creation of diet quality indices such as a priori scoring systems as they simplify analysis of adherence to the diet in relation to different primary health outcomes [50,67,72].…”
Section: Assessing Adherence To a Mediterranean Dietmentioning
confidence: 99%